Cannabidiol for neurodegenerative disorders: important new clinical applications for this phytocannabinoid?. (10th January 2013) - Fernández‐Ruiz, Javier; Sagredo, Onintza; Pazos, M. Ruth; García, Concepción; Pertwee, Roger; Mechoulam, Raphael; Martínez‐Orgado, José
<x xml:space="preserve">Abstract</x> Cannabidiol (CBD) is a phytocannabinoid with therapeutic properties for numerous disorders exerted through molecular mechanisms that are yet to be completely identified. CBD acts in some experimental models as an anti‐inflammatory, anticonvulsant, anti‐oxidant, anti‐emetic, anxiolytic and antipsychotic agent, and is therefore a potential medicine for the treatment of neuroinflammation, epilepsy, oxidative injury, vomiting and nausea, anxiety and schizophrenia, respectively. The neuroprotective potential of CBD, based on the combination of its anti‐inflammatory and anti‐oxidant properties, is of particular interest and is presently under intense preclinical research in numerous neurodegenerative disorders. In fact, CBD combined with Δ9‐tetrahydrocannabinol is already under clinical evaluation in patients with Huntington's disease to determine its potential as a disease‐modifying therapy. The neuroprotective properties of CBD do not appear to be exerted by the activation of key targets within the endocannabinoid system for plant‐derived cannabinoids like Δ9‐tetrahydrocannabinol, i.e. CB1 and CB2 receptors, as CBD has negligible activity at these cannabinoid receptors, although certain activity at the CB2 receptor has been documented in specific pathological conditions (i.e. damage of immature brain). Within the endocannabinoid system, CBD has been shown to have an inhibitory effect on the inactivation of endocannabinoids (i.e. inhibition of FAAH enzyme), thereby enhancing the action of these endogenous molecules on cannabinoid receptors, which is also noted in certain pathological conditions. CBD acts not only through the endocannabinoid system, but also causes direct or indirect activation of metabotropic receptors for serotonin or adenosine, and can target nuclear receptors of the PPAR family and also ion channels.